2014
DOI: 10.1097/fbp.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces behavioural sensitization and overexpression of cocaine-regulated and amphetamine-regulated transcript peptides in mice

Abstract: This study examined whether repeated administration of caffeine would induce behavioural sensitization and overexpression of cocaine-regulated and amphetamine-regulated transcript (CART) peptides in mice. The involvement of dopaminergic receptors and adenosine receptors in caffeine-induced behavioural sensitization and CART overexpression was studied. The relevance of D₁R and D₂R, and A₁R and A(2A)R in the overexpression of CART peptides in mouse striatum was also evaluated. Repeated administration of caffeine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…) and caffeine (Hu et al . ). In the present study, CART gene expression changed following chronic nicotine withdrawal (8 and 24‐hour timepoints).…”
Section: Discussionmentioning
confidence: 97%
“…) and caffeine (Hu et al . ). In the present study, CART gene expression changed following chronic nicotine withdrawal (8 and 24‐hour timepoints).…”
Section: Discussionmentioning
confidence: 97%
“…It was previously found that CREB activity in the NAc shell is important for the activity of psychostimulants [ 35 37 ]. After caffeine administration, CART peptides are more highly expressed in the NAc shell than in the NAc core [ 15 , 29 ]. The NAc shell is reported to have a major role in the integration of brain reward mechanisms and the functions of core structures that are engaged in motor-associated outputs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, CART peptides can regulate locomotor activity via dopamine receptor and cAMP/PKA/pCREB signaling pathway activities. Our previous report showed that cocaine- and caffeine-induced sensitization was expressed on the 5 th day of administration and that CREB phosphorylation and CART peptide expression peaked on the 5 th day [ 28 , 29 ]. In the present study, we examined the effects of CART peptides on locomotor activity and CREB phosphorylation on the 5 th day of caffeine administration.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [ 40 ] tested whether repeated CAFF administration would cause behavioral sensitization and an increased expression of CART. It did produce behavioral sensitization, and CART levels did increase and peaked at day 5 and then declined.…”
Section: Caffeinementioning
confidence: 99%